Terrorism and national security reform : how commissions can drive change during crises - Tama, Jordan, 1976- (Cambridge ; New York : Cambridge University Press, 2011)
'Terrorism and National Security Reform demonstrates that blue-ribbon commissions can be powerful vehicles for policy change, overturning the conventional wisdom that views them only as devices for passing the buck. Jordan Tama explains how the unique political credibility of commissions can enable them to forge bipartisan consensus on tough policy challenges. He also shows that commissions are most valuable during a crisis, when policymakers face pressure to make changes but frequently cannot agree on what to do. Using an original database, case studies, and more than 200 interviews of policymakers and commission participants, Tama reveals how commissions have shaped Barack Obama's plan for ending the Iraq War, spurred the largest government and intelligence overhauls since 1947, and driven many other elements of U.S. counterterrorism policy. In an era of unrelenting partisanship and extreme polarization, this book shows that commissions are increasingly valuable policymaking tools'--
Machine generated contents note: 1. Introduction: commisioning reform; Part I. Patterns of Commision Influence: 2. A theory of commision influence; 3. The impact of national security commisions; Part II. Commisions and Counterterrorism Policy: 4. Responding to the first wave of anti-American terrorism; 5. Grappling with the rise of Al Qaeda; 6. Reforming homeland security and intelligence after 9/11; Part III. Conclusion: 7. Findings, implications, and the effort to end the Iraq War.
Includes bibliographical references (p. 209-219) and index.
Includes bibliographical references and index.
Keywords: Executive advisory bodies -- United States -- Case studies; Political planning -- United States -- Case studies; National security -- United States -- Case studies; Terrorism -- Government policy -- United States -- Case studies